2021
DOI: 10.3389/fcell.2021.687522
|View full text |Cite
|
Sign up to set email alerts
|

Echinoderm Microtubule Associated Protein Like 1 Is Indispensable for Oocyte Spindle Assembly and Meiotic Progression in Mice

Abstract: Completion of the first meiosis is an essential prerequisite for producing a functionally normal egg for fertilization and embryogenesis, but the precise mechanisms governing oocyte meiotic progression remains largely unclear. Here, we report that echinoderm microtubule associated protein (EMAP) like 1 (EML1), a member of the conserved EMAP family proteins, plays a crucial role in the control of oocyte meiotic progression in the mouse. Female mice carrying an ENU-induced nonsense mutation (c.1956T > A; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 74 publications
1
5
0
Order By: Relevance
“…Indeed, we observed that MTOC integrity was reduced after AZO treatment. Similar to our observation, it has been reported that a partial decrease in MTOC integrity caused severe spindle abnormalities, but partly disturbed PBE (Wang et al, 2017;Yin et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, we observed that MTOC integrity was reduced after AZO treatment. Similar to our observation, it has been reported that a partial decrease in MTOC integrity caused severe spindle abnormalities, but partly disturbed PBE (Wang et al, 2017;Yin et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Our results suggest that significantly increased levels of p-CDK1 (Y15) are probably the causes of the meiotic defects in Lsm14b KO oocytes. Previous studies have shown that PD166285, a specific inhibitor of WEE1/2 kinases, could be able to activate MPF by reduced levels of CDK1 (Y15) phosphorylation in mouse oocytes [ 44 , 45 ]. Western blot analysis showed that PD166285 treatment dramatically reduced the levels of CDK1 (Y15) phosphorylation in Lsm14b KO GV oocytes at the end of 20 h IVM (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Low levels of MPF activity are one of the causes of PN formation and meiotic defects [ 45 ]. Our observation that the Lsm14b KO oocytes failed to assemble the MII spindle after extrusion the PB1, but instead entered the interphase and formed PN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we mainly revealed that between AC and VC of day 30 equine embryos, there are 484 differential expressed genes. Among these, 305 genes are shown specifically up-regulated in enlarging AC, and it is not surprising that these genes are mainly related to cell mitosis regulation, for example, NDC80 , NUF2 , SPC24 , and SPC25 , which compose the nuclear division cycle 80 (Ndc80) complex to influence mitosis ( Gao et al, 2020 ) and CCNB1 , EML1 , AURKB , AURKA , SPC25 , which are primarily involved in mitotic spindle organization ( Villegas et al, 2014 ; Cheng et al, 2021 ; Yin et al, 2021 ). These results could benefit our understanding of the physiological state of preimplantation AC, and the key genes and pathways controlling the AC enlargement.…”
Section: Discussionmentioning
confidence: 99%